Pengaruh, Motivasi Kerja, Dan Kemampuan Kerja Terhadap Kinerja UMKM Di Kecamatan Tanggulangin - Muhammad Aliyyuddin Salim; Wahyu Eko Pujianto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims, to test and analyze, the effect of .work motivation and work ability on the performance of MSMEs in Tanggulangin District .both partially and, simultaneously..This type of research is quantitative, the data collection method uses a structured questionnaire given to respondents and .measured using a 5-point Likert scale. The. survey population is MSMEs in Tangulangin .District. The sampling method used in this, study was non-probability sampling, the number of samples investigated was 63 sectors. The data analysis technique used in this research is the SPSS 24 application program. To ensure that the data is not biased, validity and reliability checks are carried out. The results, of the analysis show that work motivation. has a positive and significant. effect on the performance of MSMEs in Tanggulangin District, work ability .has a positive and insignificant effect on the .performance of MSMEs in Tanggulangin District, and together work motivation, and work ability .have a positive and significant effect.on the performance of MSMEs in Tanggulangin District.